(untitled) (Bangladesh Journal of Medicine, 2024)
Background: Dietary restriction of short chain fermentable carbohydrate oligosaccharides, disaccharides, monosaccharides and polyols (FODMAPs) has been found to be beneficial in alleviating gastrointestinal symptoms in diarrhea predominant irritable bowel syndrome (IBS-D) patients. This study investigated frequently reported food items with intolerance and the effects following their restriction in addition low FODMAP diet introduction in the management of IBS-D. Methods: This was an interventional study on 115 patients who met the Rome IV criteria for IBS-D, enrolled at Gastroenterology outpatient clinic in Dhaka Medical College Hospital. The participants completed a 7 days food diary & Bristol stool diary before and at the end of study, were assigned to follow a diet restricting high FODMAP & containing low FODMAP for 4 weeks. Symptoms severity was assessed using IBS symptom severity scoring questionnaire. Results: Among 115 participants, majority (95.6%) reported their symptoms related to intake of at least one of the food items, most common were dairy products (76.5%), green leafy vegetables (68.7%), junk food (49.6%), pulses (37.4%), wheat (37.4%), bottle gourd (37.4%), cauliflower (33.9%) and mango (31.3%). Dietary intervention led to greater reductions (P < .001) in average daily scores of abdominal pain frequency, severity, bloating severity, stool consistency, frequency & dissatisfaction with bowel habit compared to baseline in majority of the patients (87%). Food diaries demonstrated good adherence to dietary advice. Conclusion: The majority of IBS-D patients reported certain food items as predominant triggers of their GI symptoms. Following a low FODMAP dietary advice effectively reduced symptoms as well as improved stool consistency & frequency in IBS-D patients. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 169